The Correlation between Smoking Status and BMI with The Complaints of Musculoskeletal Disorders on Palm Farmers - Husda Oktaviannoor; Zairin Noor Helmi; Ratna Setyaningrum (International Journal of Public Health Science (IJPHS), 2015)
According a study by Research Centre and Health Ecology Development Ministry of Health in 2004, palm farmers are one of a group worker that suffers complaint musculoskeletal disorder. This research to determine the correlation between the smoking status and BMI with complaints of musculoskeletal disorders (MSDS) of palm farmers in PT. X. The method are analytic observational with the cross-sectional approach. Instruments such as questionnaires, mikrotoise, scales underfoot, check the NBM, and VAS. Research technique is use purposive sampling. Research sample of 40 respondents. Results showed 32.5% light smokers, 45% moderate smokers, and 15% of heavy smokers, 17.5% weight and 2.5% obese, and 60% had complaints of MSDs. Spearman test results, it is known there is a correlation between the smoking status with complaints of MSDs (p=0.037), there was no significant correlation between BMI with complaints of MSDs (p=0.272). It can be concluded that there is a correlation between the smoking status with MSDs complaints, but there is no correlation between the BMI with the MSDs complaints. This research is expected to be input for the company to conduct training exercises ergonomics and providing information about the importance of maintaining the health of tobacco consumption.